H3K4me3-Mediated Upregulation of LncRNA-HEIPP in Preeclampsia Placenta Affects Invasion of Trophoblast Cells - Sun, Ningxia; Chen, Huaiyan; Ma, Yan; Pang, Wenjuan; Wang, Xiang; Zhang, Qing; Gao, Lu; Li, Wen (Frontiers in Genetics, 2020)
Preeclampsia (PE) is a pregnancy-related disease defined as onset of hypertension and proteinuria after the 20th week of pregnancy, which causes most maternal and perinatal morbidity and mortality. Although placental dysfunction is considered as the main cause of PE, the exact pathogenesis of PE is not yet fully understood. Long non-coding RNAs (lncRNAs) are implicated in a broad range of physiological and pathological processes, including the occurrence of PE. In this study, we investigated the expression and functions of HIF-1α pathway–related lncRNA-HEIPP (high expression in PE placenta) in the pathogenesis of PE. The expression of lncRNA-HEIPP in the placenta from women who underwent PE was screened by lncRNA microarray and then verified using real-time polymerase chain reaction. Then, the methylation profile of the lncRNA-HEIPP promoter and the enrichment of H3K4me3 binding were assessed by bisulfite pyrosequencing and chromatin immunoprecipitation (ChIP)–quantitative polymerase chain reaction (qPCR) assay, respectively. It was found that the level of lncRNA-HEIPP in the PE placenta was significantly higher than that in normal placenta and was increased in HTR-8/SVneo human trophoblast cells upon hypoxia treatment. Moreover, we reported that H3K4me3 manifested significantly higher promoter occupancy on lncRNA-HEIPP promoter in HTR-8/SVneo cells upon hypoxia treatment and found that the downregulation of lncRNA-HEIPP promoted trophoblast invasion. Our findings suggested that the hypoxia-induced expression of lncRNA-HEIPP mediated by H3K4me3 modification in trophoblast may contribute to the pathogenesis of PE.